Book Review: Business Economics (Second Edition) - Poudel, Hom Nath (Economic Literature, 2016)
Business Economics (Second Edition) by Pramshu Nepal, Min Raj Poudel, Girdhari Prasad Lamichhne and Rishi Ram Gaire. Kathmandu: M.K. Publisher and distributers, 2012, Pages 385 (including references, old question and chapter wise question banks). Price: NRs 280. Economic Literature, Vol. XI (69-70), June 2013